The future implications of migrant labour for employment relations - McKay, Sonia (Birmingham, 2012)
"A number of factors have come into play that make it more likely that migrant workers will be present in UK workplaces in the years to come, including a likely growth in agency employment, the ageing of the UK labour force and a skills disparity. Acas commissioned Professor Sonia Mckay, from the Working Lives Research Institute to explore the implications for employment relations of the future participation of migrant workers in Britain’s workplaces. The paper examines the defi nitions and demographic profi le of migrant labour. It then goes on to explore aspects of the changing nature of the employment relationship in which many migrant workers fi nd themselves including the increase in subcontracting,agency working and posted work."